Profil Kemampuan Berpikir Kreatif Siswa SMA Menggunakan Soal Uraian Berbasis Pemecahan Masalah pada Materi Energi Terbarukan - Fithrunnada, Fithrunnada; Sunarti, Titin (IPF: Inovasi Pendidikan Fisika, 2023)
This study aims to describe the profile of high school students' creative thinking abilities by using a creative thinking ability assessment instrument based on problem solving in renewable energy materials. The instrument is in the form of a description with reference to indicators of creative thinking (fluency, elaboration, originality, and flexibility) and the polya problem solving stage (understanding the problem, making plans, implementing plans, and seeing or re-examining). The instruments used were developed using the ADDIE development model (Analysis, Design, Develop, Implement, and Evaluate) and the data collection techniques used tests and questionnaires. The sample of this research was 60 students of class X MA Matholi'ul Anwar Lamongan for the 2022/2023 academic year. The results of the implementation of the instrument showed that the level of creative thinking ability of class X students of MA Matholi'ul Anwar Lamongan was 32% categorized as quite creative and 68% categorized as creative. The ability of students in each indicator to think creatively obtained the highest to the lowest score respectively on the aspects of fluency, elaboration, originality, and flexibility. The results of the analysis of the creative thinking ability profile of class X students of MA Matholi'ul Anwar Lamongan are categorized as quite creative and creative. Keywords: Creative Thinking Ability, Problem Solving.